In vitro mutation breeding of chrysanthemum (Dendrathema grandifolia Tzvelev.) cv. pink Repin - Latado, Rodrigo Rocha; Tulmann Neto, Augusto; Mendes, Beatriz M.J. (Pesquisa Agropecuaria Brasileira, 1996)
This study aimed to adapt and utilize in vitro mutagenesis technology for genetic improvement of chrysanthemum. Pedicels were obtained from immature floral buds of chrysanthemum cv. pink Repin, and sensitivity to gamma radiation was determined. Pedicels were then irradiated at a dose of 8 Gy of gamma-rays. The irradiated and non-irradiated control pedicels were cultured under previously determined organogenesis culture medium. Plants regenerated were grown in the greenhouse and the evaluation was done during the flowering period. Forty six mutants for flower colour were selected from the irradiated pedicels (colours: bronze, champagne, dark pink and pale pink), and another mutant showed variegated leaves. Each colour mutant developed inflorescences with a single colour, indicating that the method is efficient for the obtention of periclinal or solid mutants, in chrysanthemum.